การพัฒนามาตรฐานศูนย์วิทยบริการ สถาบันการพลศึกษา - พิพิธธนชัย, อนุเศรษฐ์; พาวินันท์, ประภาส; พันธุ์เมฆา, พวา (บรรณศาสตร์ มศว, 2017)
บทคัดย่อ การวิจัยครั้งนี้มีจุดมุ่งหมายเพื่อพัฒนามาตรฐานศูนย์วิทยบริการ สถาบันการพลศึกษา โดยใช้ระเบียบวิธีวิจัยแบบเดลฟาย โดยใช้แบบสอบถามแบบมาตรประมาณค่า 5 ระดับและคำถามปลายเปิดเป็นเครื่องมือในการเก็บรวบรวมข้อมูลจากผู้เชี่ยวชาญ จำนวน 17 คน ประกอบไปด้วย ผู้เชี่ยวชาญด้านบรรณารักษศาสตร์และสารสนเทศศาสตร ์ ด้านพลศึกษาและสุขศึกษา ด้านวิทยาศาสตร์การกีฬาและสุขภาพ และด้านการจัดการกีฬาและนันทนาการ ส่วนสถิติที่ใช้ในการวิเคราะห์ข้อมูล คือ ค่ามัธยฐานและค่าพิสัยระหว่างควอไทล์ โดยนำข้อมูลมาจัดกลุ่มและสรุปเป็นมาตรฐานศูนย์วิทยบริการสถาบันการพลศึกษา ผลการวิจัย พบว่า ผู้เชี่ยวชาญมีความคิดเห็นสอดคล้องกันเกี่ยวกับมาตรฐานศูนย์วิทยบริการ สถาบันการพลศึกษา ในระดับที่ยอมรับได้ จำนวน 57 ข้อ จากจำนวนทั้งหมด 58 ข้อ ของมาตรฐานทั้ง 7 ด้าน ได้แก่ ด้านโครงสร้างและบริหาร ด้านงบประมาณและการเงิน ด้านบุคลากร ด้านทรัพยากรสารสนเทศ ด้านอาคารสถานที่และครุภัณฑ์ ด้านการบริการ และด้านความร่วมมือระหว่างห้องสมุด Abstract In this thesis, the researcher describes and analyzes the development of standards forthe Academic Services Centers under the jurisdiction of the Institute of Physical Education. Incarrying out this project, the researcher relied on the Delphi technique through employing afive-rating scale questionnaire and open-ended questions as instruments for collecting datafrom seventeen experts. These experts were in the fields of library and information science,physical education and health education, sports science and health, and sports managementand recreation. In data analysis, the researcher utilized the statistical techniques of medianand interquartile range. The data collected were categorized and summarized in a form asstandards for Academic Services Centers, Institute of Physical Education. Findings showed thatthe opinions of the experts were mutually congruent concerning appropriate standards for theAcademic Services Center at an acceptable level of 57 items from a total of 58 items in thefollowing seven aspects: structure and administration, budget and finances, personnel, informationresources, buildings and durable goods, services, and inter-library cooperation.